Aloha Potter! - Talley, Linda, 1948-; Chase, Andra, 1942- (Kansas City, Mo. : MarshMedia, 2004)
In the coral reefs off the Hawaiian Islands, Potter the angelfish and his friends learn to cope with the persistent teasing of Alakuma the crab.
Map on endpapers.
2.8
K-3
Keywords: Fishes -- Fiction; Crabs -- Fiction; Teasing -- Fiction; Behavior -- Fiction; Hawaii -- Fiction; Fishes -- Fiction; Crabs -- Fiction; Teasing -- Fiction; Behavior -- Fiction; Hawaii -- Fiction